A study on factors influence consumers purchase intention towards green marketing awareness among university students in Melaka / Sheilla Afiqah Ab Rahim - Ab Rahim, Sheilla Afiqah (Faculty of Business and Management, 2019)
This research study is to identify on factor influence consumers’ purchase intention towards green marketing awareness among university students in Melaka. The factor were awareness of green marketing, awareness of price, awareness of eco-label and consumers’ environmental concerns. This study research framework adapted from Norazah (2013) and Sathiswaran, Azlinda & Nurul (2014). Futhermore, this study were using conveniece sampling technique and questionnaires were distributed to university students in Melaka via Google From. A 110 respodents had been answered the questionnaire. Collected data were analysed using Statistical Package for Social Science (SPSS) version 22. Hence, the data were obtained from descriptive analysis, frequency distribution, reliability analysis and multiple regression analysis. The results show that awareness of green marketing, awareness of price and consumers’ environmental concerns are significantly influenced the consumers’ purchase intention while awareness of eco-label is not significantly. As conclusion, these findings would be useful for future researchers, marketers, government and non-government to improve green campaign in Malaysia.